FINANCIAL RESOURCES OFFERED BY BANKS TO AGRICULTURAL COOPERATIVES AND SUGGESTIONS FOR IMPROVING THESE FINANCIAL RESOURCES (Third Sector Social Economic Review, 2017)
Agricultural cooperatives are neccessary elements for agricultural and rural development. There are many examples of the positive contribution of agricultural cooperatives  to their members and countries.While some of these cooperatives purchase products from their partners, there are cooperatives that sell services to their members such as irrigation cooperatives. With these different economic activities, cooperatives have different cash flows. Cooperatives have to sustain their activities with sufficient financial resources. The fact that cooperatives do not have sufficient internal financial resources constantly. Therefore external financial resources are needed. External financial resources have their own characteristics. Credits are offered as working capital generally have fewer than one-year bucks, while investment capital can have up to 7 years. On the other hand, many problems arise during the access to these resources. Generally, the problems are the incompatibility of the maturity / reimbursement structure of the cooperative's cash flow with the financial resources provided by the bank and the credit guarantees requested are incompatible with the cooperative legal entity. Moreover, the steps of making a loan application, getting results and using credit are much more difficult than with individual financing. Banks must understand the cash flow of cooperatives very well and act on the added value provided by the approach of financing third parties in this value chain. On this basis, the cash flow between cooperatives and suppliers will be evaluated positively, which will naturally lead to the transfer of more resources to cooperatives by making a positive contribution to the risk perception of banks.
Keywords: Agricultural cooperatives; banking; financial resources; loans